Claims Relating to Premises of a Diplomatic Mission Case (Tyngene s.r.o. v. Municipal District Prague—Troja and the Republic of Korea—Embassy of the Republic of Korea). (2022) - Unknown
Abstract : 346 State immunity — Jurisdiction — Property — Functional nature of immunity — Acta jure imperii and acta jure gestionis — Immunity confined to acta jure imperii — Failure of lower courts to take this limitation into account — Premises of a diplomatic mission — Korean Embassy in Prague — Whether Republic of Korea immune from proceedings in Czech courts Diplomatic relations — Immunity — Property — Korean Embassy in Prague — Whether Republic of Korea immune from proceedings in Czech courts — Whether Korean Embassy unjustly enriched — Whether immovable property used for purposes of State's diplomatic mission — Inviolability of premises of diplomatic mission and performance of mission's functions — Vienna Convention on Diplomatic Relations, 1961, Article 22 — United Nations Convention on Jurisdictional Immunities of States and Their Property, 2004, Article 13 — Whether first instance decision correct — The law of the Czech Republic